Understanding the Role of Maternal Mental Health in Pregnancy and Postpartum Depression (Indian Journal of Public Health Research & Development, 2025)
Objective: This study aimed to investigate the dynamics of maternal mental health during pregnancy and the postpartum period, examining the prevalence of mental health disorders, changes over time, and the role of social support.Methods: A longitudinal study design was employed, with a sample of 80 pregnant women recruited from obstetrics and gynaecology clinics. Participants completed standardized measures assessing depressive symptoms, anxiety levels, stress, and perceived social support at multiple time points from the second trimester to twelve months postpartum. Qualitative interviews were also conducted to explore participants' subjective experiences.Results: The study found high prevalence of depressive symptoms, anxiety, and stress during pregnancy and the postpartum period. Depressive symptoms decreased over time, while anxiety and stress remained stable. Perceived social support was associated with better mental health outcomes. Qualitative analysis revealed diverse emotional experiences of pregnancy and coping strategies employed by participants.Conclusion: Addressing maternal mental health is crucial for comprehensive perinatal care. Routine screening, early intervention, and fostering social support networks are essential for promoting maternal well-being.
Keywords: Maternal mental health, pregnancy, postpartum period, social support.